SOCIETY PARTICIPATION IN DEVELOPMENT OF MARITIME TOURISM AREA OF NYANG-NYANG ISLAND IN SOUTH WEST SIBERUT DISTRICT MENTAWAI ARCHIPELAGO REGENCY - PERAWATI, DIAN; Drs. Edi Suarto, M.Pd, Drs. Edi Suarto, M.Pd; S.Si, M.Sc, Farida (STKIP PGRI Sumbar, 2014)
AbstractThis research aim to to get information and data to, studying and analysing about Society Participation in Development of Maritime Tourism Area of Nyang-Nyang Island in South West Siberut District Mentawai Archipelago Regency in seeing from 1) Hygiene 2) Security 3) Hospitality 4) Accomodation Object in research area. This Research type is research qualitative, is to analyse in depth about the phenomenon in the society. Technique intake of informan by Â purposive sampling ( directing). Data which in using that secondary and primary data. secondary data which in getting from related partiess that is: Statistical Body Center ( BPS), library, and internet. While primary data that is data which in collecting to pass/through observation, interview, and photos which in taking in field. Result of research of field show 1) Society participation in development of tourism area seen from hygiene of goodness environment have is no more of raucous garbage 2) Society participation in development of tourism area seen from security have no more awake of theft that happened, while security in sea still not yet in form by On duty tourism 3) Society participation in development of tourism area seen from society hospitality very good, all society in area of wisata always show audience hold up in conversing, and manner in behaving 4) Society participation in development of tourism area seen fromÂ accomodation were very less, need addition of homestay again in object area in the tourism area.Â